Altered phenotype in LMAN1-deficient mice with low levels of residual LMAN1 expression - Everett, Lesley A.; Khoriaty, Rami N.; Zhang, Bin; Ginsburg, David (Blood advances, 2020)
Combined deficiency of coagulation factors V and VIII (F5F8D) is an autosomal recessive bleeding disorder caused by loss-of-function mutations in either LMAN1 or MCFD2. The latter genes encode 2 components of a mammalian cargo receptor that facilitates secretion of coagulation factor V (FV) and factor VIII (FVIII) from the endoplasmic reticulum (ER) to the Golgi via coat protein complex II vesicles. F5F8D patients exhibit FV and FVIII levels that are ∼10% to 15% of normal. We report herein a comparative analysis for a series of murine Lman1 alleles. Consistent with previous reports, mice completely deficient in LMAN1 (Lman1−/−) exhibit ∼50% FV and FVIII levels. In contrast, mice carrying a hypomorphic Lman1 allele (Lman1cgt/cgt) that expresses ∼6% to 8% of wild-type Lman1 mRNA levels exhibit intermediate plasma FV and FVIII reductions (∼70% of wild-type levels). Lman1−/− mice exhibit ER accumulation of another LMAN1 cargo, alpha-1 antitrypsin (A1AT), with an intermediate level of A1AT ER retention observed in Lman1cgt/cgt mice. Finally, the previously reported strain-specific, partially penetrant, perinatal lethality of LMAN1-deficient mice (Lman1gt1/gt1) was confirmed in Lman1−/− mice, although it was not observed in Lman1cgt/cgt mice. Taken together, these results show a dose-dependent effect of residual LMAN1 on the secretion of its cargo proteins. The results also suggest that human subjects with hypomorphic LMAN1 mutations might present with mild bleeding phenotypes resulting from more modest reductions in FV and FVIII, which could be missed by routine clinical evaluation. Finally, these findings suggest that therapeutic targeting of LMAN1 to reduce FV and FVIII as an anticoagulant strategy may only require partial inhibition of LMAN1 function. •There is a dose–response relationship between Lman1 expression level and secretion levels of LMAN1 cargoes in mice (FV, FVIII, and A1AT).•Therapeutic targeting of LMAN1 to reduce FV and FVIII as an anticoagulant strategy may only require partial inhibition of LMAN1 function. [Display omitted]